Quantitative Insights on Enhancing Narrative Writing with Powtoon: Wawasan Kuantitatif tentang Meningkatkan Penulisan Narasi dengan Powtoon - Pramesti, Melinda Widyadana Dwi; Megawati, Fika (Indonesian Journal of Innovation Studies, 2024)
This quantitative study investigates the impact of integrating Powtoon media into English language education to improve ninth-grade students' narrative text writing skills. The research, conducted in a single class at MTs Muhammadiyah 1 Taman, involved 26 students selected through purposive sampling. Pre-tests and post-tests were administered before and after using Powtoon, with findings indicating a significant enhancement in students' grammar, vocabulary, and narrative coherence. The study highlights Powtoon's potential as an engaging educational tool to address learning challenges and improve language learning outcomes, recommending further content development for future research and teaching practices. Highlight: Powtoon improves narrative writing. Quantitative study shows effectiveness. Emphasizes need for content expansion. Keyword: Powtoon media, narrative text writing, language education, ninth-grade students, quantitative study